2011
DOI: 10.1088/0954-3899/38/5/053001
|View full text |Cite
|
Sign up to set email alerts
|

Determining pseudoscalar meson photoproduction amplitudes from complete experiments

Abstract: Abstract.A new generation of complete experiments is focused on a high precision extraction of pseudoscalar meson photo-production amplitudes. Here, we review the development of the most general analytic form of the cross section, dependent upon the three polarization vectors of the beam, target and recoil baryon, including all single, double and triple-polarization terms involving 16 spin-dependent observables. We examine the different conventions that have been used by different authors, and we present expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
180
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(182 citation statements)
references
References 41 publications
(213 reference statements)
2
180
0
Order By: Relevance
“…Additionally, polarisation information can be accessed with these probes, with the effects of polarisation on the reaction particles giving new insights into the properties of resonances, and more ways to find evidence of their existence [14].…”
Section: Resolving the Missing Resonance Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, polarisation information can be accessed with these probes, with the effects of polarisation on the reaction particles giving new insights into the properties of resonances, and more ways to find evidence of their existence [14].…”
Section: Resolving the Missing Resonance Problemmentioning
confidence: 99%
“…Detailed investigations have demonstrated that measurement of the cross-section, σ 0 , and single polarisation observables Σ, T and P, as well as four appropriately chosen double polarisation observables (of which there are several examples) can determine the reaction amplitudes without ambiguities [19,20], however, the available data and associated uncertainties do not provide sufficient constraint to eliminate these ambiguities and more than eight measurements will be needed [14].…”
Section: Polarisation Observablesmentioning
confidence: 99%
“…Following the notation of [7] the differential cross section for a circularly polarized photon beam and a transversally polarized target reads…”
Section: Introductionmentioning
confidence: 99%
“…To ensure data are correctly incorporated into partial wave arXiv:1108.5411v2 analyses, we encourage experimental groups to specify their sign convention relative to Table 1 1. Names for the coordinate-independent polarization ratios as used in the partial wave analyses of the groups from MAID [2], SAID [3], Bonn-Gatchina (BoGa) [4], Carnegie Mellon (CMU) [5] and JLab-EBAC [1]. MAID, SAID CMU SHKL-EBAC, BoGa R S " " "…”
mentioning
confidence: 99%